Assessment of Infantile Hemangiomas Using a Handheld Wireless Diffuse Optical Spectroscopic Device. Issue 4 (26th May 2017) - Fong, Christopher J.; Garzon, Maria C.; Hoi, Jennifer W.; Kim, Hyun K.; Lauren, Christine T.; Morel, Kimberly; Geller, Lauren; Antonov, Nina; Weitz, Nicole; Wu, June; Hielscher, Andreas H.
Abstract: Background/Objectives: Infantile hemangiomas (IHs) are vascular tumors with the potential for significant morbidity. There is a lack of validated objective tools to assess IH severity and response to treatment. Diffuse optical spectroscopy (DOS), a noninvasive, nonionizing imaging modality, can measure total hemoglobin concentration and hemoglobin oxygen saturation in tissue to assess IH vascularity and response to treatment. Our objective was to evaluate the utility of a wireless, handheld DOS system to assess IH characteristics at selected points during their clinical course. Methods: Thirteen subjects (initial age 5.8 ± 2.0 mos) with 15 IHs were enrolled. IHs were classified as proliferative, plateau phase, or involuting. Nine patients with 11 IHs were untreated; four patients with 4 IHs were treated with timolol or propranolol. Each IH was evaluated by placing the DOS system directly on the lesion as well a normal contralateral skin site. IH vascularity and oxygenation were scored using a newly defined normalized hypoxia fraction (NHF) coefficient. Measurements were recorded at various intervals from the initial visit to 1 to 2 years of age. Results: For the nine untreated IHs, the NHF was highest at 6 months of age, during proliferation. Differences in NHFs between the proliferation and the plateau (p = 0.02) and involuting (p < 0.001) stages were statistically significant. In treated patients, the NHF normalized to 60% after 2 months. One treated IH came within 5% of the NHF for normal skin after 12 months. Conclusions: DOS can be used to assess the vascularity and tissue oxygenation of IHs and monitor their progression and response to treatment.